Pulsed ultrasound modulated optical tomography with harmonic lock-in holography detection - Ruan, Haowen; Mather, Melissa; Morgan, Stephen P. (Optical Society of America, 2013)
A method that uses digital heterodyne holography reconstruction to extract scattered light modulated by a singlecycle ultrasound (US) burst is demonstrated and analyzed. An US burst is used to shift the pulsed laser frequency by a series of discrete harmonic frequencies which are then locked on a CCD. The analysis demonstrates that the unmodulated light’s contribution to the detected signal can be canceled by appropriate selection of the pulse repetition frequency. It is also shown that the modulated signal can be maximized by selecting a pulse sequence which consists of a pulse followed by its inverted counterpart. The system is used to image a 12 mm thick chicken breast with 2 mm wide optically absorbing objects embedded at the midplane. Furthermore, the method can be revised to detect the nonlinear US modulated signal by locking at the second harmonic US frequency. © 2013 Optical Society of America